2017
DOI: 10.12956/tjpd.2017.312
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Children with Acute Bacterial Meningitis Treated in Two Separate Time Periods in Turkey

Abstract: ÖZETAmaç: Bakteriyel menenjit tıbbi acil bir durumdur. Tedavi edilmemiş bakteriyel menenjitlerde mortalite oranı %100'dür. Çalışmada, Türkiye'de Haemophilus influenzae tip b ve Streptococcus pneumoniae'ya karşı geliştirilmiş konjuge aşıların Ulusal Bağışıklama Programı'na girmesinden önce ve sonra, 2 farklı dönemde, 2 farklı merkezde izlenen akut bakteriyel menenjitler değerlendirilerek, Türkiye'de yıllar içinde akut bakteriyel menenjit epidemiyolojisi, tedavi seçenekleri, komplikasyon oranlarındaki değişiklik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Septic shock was reported in approximately 40% of patients in the studies from the EM region, while hemodynamic disorder/sepsis were reported in over half of patients in the study from the NA region. Data on post-discharge complications and sequelae were available from eight EM region studies (Kuwait n = 2 [ 93 , 94 ]; Qatar n = 2 [ 52 , 69 ]; Saudi Arabia n = 2 [ 53 , 71 ]; and Turkey n = 2 [ 98 , 99 ]) and two NA region studies (Egypt n = 1 [ 78 ] and Tunisia n = 1 [ 89 ]). The majority of studies in the EM region reported non-specified sequelae; there was little overlap across studies in terms of specific reported events for either region.…”
Section: Objective 3: Imd Presentation and Managementmentioning
confidence: 99%
“…Septic shock was reported in approximately 40% of patients in the studies from the EM region, while hemodynamic disorder/sepsis were reported in over half of patients in the study from the NA region. Data on post-discharge complications and sequelae were available from eight EM region studies (Kuwait n = 2 [ 93 , 94 ]; Qatar n = 2 [ 52 , 69 ]; Saudi Arabia n = 2 [ 53 , 71 ]; and Turkey n = 2 [ 98 , 99 ]) and two NA region studies (Egypt n = 1 [ 78 ] and Tunisia n = 1 [ 89 ]). The majority of studies in the EM region reported non-specified sequelae; there was little overlap across studies in terms of specific reported events for either region.…”
Section: Objective 3: Imd Presentation and Managementmentioning
confidence: 99%